Skuteczność poprawek parlamentu europejskiego w procedurze (specjalnej procedurze ustawodawczej) (Politeja, 2015)
Effectiveness of the European Parliament Amendments in the Consultation Procedure (Special Legislative Procedure)The aim of the article is to empirically analyze the effectiveness of the European Parliament’s amendments in one of the special legislative procedures, namely consultation. In the first step, several hypotheses were developed predicting positive or negative impact of certain factors on the EP amendments success. Subsequently, those suppositions were quantitatively tested by logistic regression on special dataset representing 599 legislative acts adopted during the fifth and sixth parliamentary term, that is, between 1 May 1999 and June 2009, under consultation. The results revealed that the EP is more likely to be successful in this procedure if it implements five strategies. Firstly, it seeks to conclude a package deal, that is, it links a consultation decision to a codecision or budgetary proposal. Secondly, it delays its opinion on a legislative proposal. Thirdly, it persuades the European Commission to support its amendments. Fourthly, it prolongs legislative negotiations with the Council until the end of parliamentary term. Fifthly, it accumulates all its negotiation resources on salient proposals. In addition, the EP is more likely to succeed in consultation when it proposes democratic and financial amendments, whereas it is least likely to be successful when it tables institutional issues. The success of EP amendments is also significantly greater in directives than in regulations, decisions or framework decisions. On the other hand, voting rule in the Council, rapporteur experience and her/his political affiliation with EPP‑ED, PES or ELDR/ALDE don’t have any impact on the EP amendments success.